Eastern Virgin Hinterlands: Formative Period (AD 700–AD 1225) Settlement Practices in Grand Canyon National Park. Issue 4 (2nd October 2019) - Mink, Philip
Abstract : Grand Canyon National Park encompasses a large portion of the southeastern extent of the Virgin Ancestral Puebloan tradition. From AD 700 to 1225, the region also bounded the Kayenta Ancestral Puebloan and the Cohonina traditions. This paper examines variation in settlement practices between these three traditions in this ecologically diverse locale. The analyses provide new insights and settlement models for the Formative Period in Grand Canyon National Park.